A haplotype-phased genome characterizes the genomic architecture and causal variants for RXf1 conferring resistance to Xanthomonas fragariae in strawberry (F. × ananassa) - Jin-Hee Kim; Vance M. Whitaker; Seonghee Lee (BMC Genomics)
Abstract Background Cultivated octoploid strawberry (Fragaria × ananassa) is one of the most economically important fruits worldwide due to its flavor, texture, and health benefits. However, bacterial angular leaf spot (ALS) causes economic losses in fruit production and plant nurseries. All commercial strawberry varieties are susceptible to ALS. A major resistance locus, RXf1, has been reported, but the genomic structure and candidate genes underlying this resistance remain known. Results Fine-mapping was performed using three segregating populations containing 663 individuals that were genotyped with subgenome specific seven high-resolution melting (HRM) markers to narrow the RXf1 region to a 486-kb interval on chromosome 6C. We assembled a haplotype-phased chromosome-scale genome of ALS-resistant breeding selection FL17.68–110 using highly accurate long-read sequencing and trio-binning with parental short reads. The 1.62 Gbp genome containing two haplotypes, 56 chromosomes and 193,072 annotated genes. Transcriptome analysis in response to the ALS pathogen identified a candidate gene, Resistance gene analogue 3 (RGA3), associated with the RXf1 resistance. The gene structure and sequence variations within Fa RGA3 were identified between resistant and susceptible genotypes. Conclusions Our results narrowed the RXf1 region, identified structural variations within this locus and pointed to Fa RGA3 as a promising candidate gene. This information will be useful for breeders toward developing ALS-resistant strawberry varieties, and the high-quality genome will be a valuable resource for further genomics research in octoploid strawberry.